Eisenmenger syndrome presenting with chronic thromboembolic disease - Pazarlı, Ahmet Cemal; Karaman, Kayıhan; Yıldırım, Tuğba (The European Research Journal, 2024)
Eisenmenger syndrome is characterized by the reversal of blood flow due to increased pulmonary vascular resistance. It can be prevented with early diagnosis and surgical treatment. Thromboembolism is a leading cause of death in patients with Eisenmenger syndrome. Pulmonary endarterectomy is the primary treatment, but medical treatments may be considered in inoperable cases. Regular follow-up and a multidisciplinary approach are important for diagnosis and treatment. Lifestyle changes and medical therapy can improve patient’s quality of life and prevent complications. Our case is presented because of the chronic thromboembolic disease in addition to the pulmonary hypertension due to the partial atrioventricular septal defect and the management of the treatment.